THE INFLUENCE OF USING MNEMONICS TECHNIQUE TOWARDS STUDENTS’ VOCABULARY MASTERY - Sinta Novia (JETA (Journal of English Teaching and Applied Linguistic), 2020)
The research was aimed to know the influence of Mnemonic Technique towards students’ vocabulary mastery, and to know whether or not the average score of the students’ vocabulary mastery which is taught by using Mnemonic Technique. In conducting the research, the writer used experimental method. The population in this research were the students at the second semester of eighth class at MTs Negeri 1 Tanjung Karang 319 students in 9 classes. The sample of this research was two classes, one class was VIII KK as experimental class there were 30 students, and another class was VIII F as the control class there were 31 students. In determining the sample, the writer used cluster random sampling technique. In collecting the data, the writer used vocabulary test. In analyzing the data the writer used t-test formula. Based on the data analysis, the students who were taught Mnemonic technique get higher score than those who were taught translation technique. It can be seen from calculating of the result of the hypothesis testing and average score of the experimental class that was higher than the control class. The average score of experimental class is 74.66 and the average score of the control class is 70.53. it also can be seen at the significant level 0.01 and 0.05 the ttest is higher than ttable (ttest ttable),that is 2.73 > 1.68 for significant level 0.01 and 2.73 > 2.02 for significant level 0.05. Therefore, substitution strategy gave the positive influence of Mnemonic technique towards students’ vocabulary mastery at the eighth class of MTs Negeri 1 Tanjung Karang in 2017/2018.